Enhancing Resilience in Geological Heritage Tourism: A Post-COVID Strategy for "Kayangan Api" and its Contribution to Environmental Development in Bojonegoro Regency, Indonesia - Megawati, Suci; Fadiyah Hidayat, Melda; Syamsul, Muhammad Rezky (JPSI (Journal of Public Sector Innovations), 2023)
The COVID-19 pandemic has devastated the tourism industry in various places worldwide. After the pandemic, many local governments that rely on tourism as their source of income have tried to recover from the crisis and improve their tourism management. Therefore, this study aims to analyse the resilience strategies of Kayangan Api tourism after COVID-19 and its contribution to environmental development in Bojonegoro Regency. This research is descriptive with a qualitative approach. This research was conducted from June to August 2023. This study focuses on the resilience strategies of Kayangan Api tourism after COVID-19. Data collection was carried out by interviewing the respective government officers responsible for managing the Kayangan Api tourist attraction and the business actors around the tourist attraction. The results of the study show that the Kayangan Api geoheritage tourism resilience strategies were carried out by improving the quality of attractions, amenities, and accessibility. This research proposes recommendations for the need for innovation, multi-actor support, and resources to optimize the existing resilience strategies in tourism development, especially in restoring tourism conditions after COVID-19 and contributing to environmental development.